Novel Spark Method for Deposition of Metal Oxide Thin Films: Deposition of Hexagonal Tungsten Oxide - Dimitrios Louloudakis (2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Hexagonal tungsten trioxide (WO3) layers are grown on indium tin oxide (ITO) substrates using a novel spark deposition system. The effects of deposition time, substrate temperature, and oxygen (O2) flow rate through the chamber on the structural and morphological characteristics as well as the electrochemical response of the layers are examined. It is found that a deposition temperature of 400 °C and O2 flow rate at 60 mL min−1 through the chamber can result in hexagonal WO3 with improved crystallinity and quite effective electrochemical/electrochromic response.